DEVELOPING LANGUAGE SCAFFOLDING MATERIALS FOR ARGUMENTATIVE WRITING: AN IDEA FOR TEACHING INTERMEDIATE WRITING SKILLS - Refnaldi, Refnaldi (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2018)
Materials are generally used to provide a stimulus to writing or discussion, as a starting point for language input and analysis, and as ideas for organizing lesson activities. In EFL context, materials play particular important roles because they may be the only contact that learners have with English and offer the only opportunities for them to study target texts. One of the important roles of instructional materials is to provide the foundation for learners’ understandings of writing and language use. They are often used to present a focus for language, such as to scaffold learners’ evolving control of different texts. Materials that assist learners toward producing clear and accurate sentences and cohesive texts are obviously very important when learning to write. This paper aims at discussing the development of language scaffolding materials in the writing activity which is based on the genre-based approach. “Scaffolding” in this case is the activity to provide any kind of support for students while they are establishing their understanding of a text and their linguistic competence to create the text. The materials provide input, tasks, and instruction that can be used to encourage and as well as to challenge students. The discussion will be focused on developing materials on four main steps of scaffolding for students of English Department. They are language familiarization, model analysis and manipulation, controlled composition, and guided composition.